Reliability and Responsiveness Drive Patient Satisfaction Among National Health‑Insurance Users at a Primary Health‑Care Center - Nur Masdalifah; Eka SR. Sihombing; Sondang Sidabutar; Peterson Yosua Silaen; Arfyah Sagita Yunanda; Inri Monika (Jurnal Penelitian Kesehatan SUARA FORIKES, 2026)
Patient satisfaction is a critical indicator of service quality in primary health‑care settings and plays an essential role in strengthening the effectiveness of the national health‑insurance program. Physical facilities, service reliability, staff responsiveness, and professional assurance are widely recognized as core determinants of patient experience. This study was conducted to analyze the level of satisfaction among national health‑insurance users at the Bane Primary Health‑Care Center in Pematangsiantar in 2024 across four dimensions of service quality. The study employed a quantitative cross‑sectional design involving 98 respondents selected using the Slovin formula. Data were collected through structured questionnaires and analyzed descriptively. The results show varying levels of satisfaction across the four dimensions. Satisfaction was highest for reliability (70.4%) and responsiveness (65.8%), indicating that patients generally perceived the services as accurate, consistent, and delivered with adequate promptness. Tangible aspects also contributed positively, with 61.2% of patients expressing satisfaction, although limitations in physical facilities and equipment remained evident. Assurance demonstrated the lowest satisfaction level (47.1%), reflecting concerns about staff competence, communication clarity, and the ability to instill confidence. In conclusion, the findings highlight the need to strengthen physical infrastructure and enhance professional assurance while maintaining reliable and responsive service delivery. Improving these dimensions may contribute to higher patient satisfaction and support the overall effectiveness of the national health‑insurance system.Keywords: patient satisfaction; tangible; reliability; responsiveness; assurance; primary health care